2007
DOI: 10.1073/pnas.0702943104
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cε is a nexus for Rho and Rap-mediated G protein-coupled receptor-induced astrocyte proliferation

Abstract: Phospholipase C (PLC ) has been suggested to transduce signals from small GTPases, but its biological function has not yet been clarified. Using astrocytes from PLC -deficient mice, we demonstrate that endogenous G protein-coupled receptors (GPCRs) for lysophosphatidic acid, sphingosine 1-phosphate, and thrombin regulate phosphoinositide hydrolysis primarily through PLC . Stimulation by lysophospholipids occurs through Gi, whereas thrombin activates PLC through Rho. Further studies reveal that PLC is required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 36 publications
6
96
0
Order By: Relevance
“…PLC-ε induced PDGF-dependent cell growth in BaF3 cells overexpressing PDGF receptor (198) or EGF-dependent cell growth in HEK293 cells or MEF cells (197,206). A recent report indicates that thrombin-dependent astrocyte proliferation is mediated by PLC-ε (207). In that report, GEF activity of PLC-ε was required for the Erk activation and cell astrocyte proliferation.…”
Section: Plc-ε Is Involved In Cell Proliferationmentioning
confidence: 86%
“…PLC-ε induced PDGF-dependent cell growth in BaF3 cells overexpressing PDGF receptor (198) or EGF-dependent cell growth in HEK293 cells or MEF cells (197,206). A recent report indicates that thrombin-dependent astrocyte proliferation is mediated by PLC-ε (207). In that report, GEF activity of PLC-ε was required for the Erk activation and cell astrocyte proliferation.…”
Section: Plc-ε Is Involved In Cell Proliferationmentioning
confidence: 86%
“…4C,D). Next, we used adenoviruses expressing PLCe variants deficient either in PLC activity or in Ras-binding (previously described in Citro et al, 2007;Oestreich et al, 2007) to rescue PDGF-BB-mediated chemotaxis in PLCe null fibroblasts. We observed that the expression of a PLCe variant that cannot bind Ras (Ad-RAm) restored chemotaxix of PLCe KO cells as well as the expression WT PLCe (Fig.…”
Section: Phospholipase C Activity Of Plce Is Required For Normal Chemmentioning
confidence: 99%
“…On the other hand, Wang and Reiser (2003) reported that thrombin/PAR-1 uses Ca 2ϩ and PKC-dependent Pyk2 to activate Src, thereby leading to ERK1/2 activation in rat astrocytes, suggesting that Ca 2ϩ signaling may regulate MAPK pathway. In this context, Citro et al (2007) reported that there are two pathways in thrombininduced astrocytic ERK activation; G q/11 /PLC␤/DAG/PKC pathway and G 12/13 /Rap1/B-Raf/PLC pathway, in which the former is involved in transient ERK phosphorylation and the latter in long-term sustained ERK phosphorylation, implying that the relationship between thrombin/PAR-1-induced MAPKs activation and resultant Ca 2ϩ signaling in astrocytes could be more complicated. Future studies are needed to determine the detailed molecular pathways that TRPC3-mediated Ca 2ϩ signaling may regulate.…”
Section: Par-1-induced Astrocytic Responsesmentioning
confidence: 99%
“…In this context, Sorensen et al (2003) reported that PAR-1 agonist peptide-induced astrocytic proliferation is inhibited 80% in the presence of Y27632, a specific inhibitor of Rho kinase activity that is profoundly involved in the regulation of astrocytic morphology. Exoenzyme C3 from Clostridium botulinum, a cell-permeable Rho inhibitor, inhibits both astrocyte morphological changes (Höltje et al, 2005) and thrombininduced astrocyte proliferation (Citro et al, 2007). Moreover, Y27632 inhibits both morphological changes and proliferation induced by thromboxane A 2 receptor agonist in astrocytoma cells (Honma et al, 2006), suggesting that the morphological change is an initial phenomenon and a universal feature of proliferating astrocytes.…”
Section: Par-1-induced Astrocytic Responsesmentioning
confidence: 99%